2017
DOI: 10.21608/eajb.2017.12150
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Certain Popular Food Products to the German Cockroach, Blattella germanica, Adults under Field Conditions

Abstract: The attractiveness of twenty seven materials (11 of fresh vegetables, 8 of plant seeds, and 8 of oily materials) to adult male and female of German cockroaches, Blattella germanica, was evaluated singly and as mixtures under field conditions. The comparison of attractiveness was done between materials in the same group and between the most attractive materials of each group. Results showed that fresh coriander leaves, dill leaves, and zucchini fruit were the most attractive materials of the green vegetables gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, the results of our food consumption analysis showed that very little peanut butter, especially the roasted form, was eaten, although Khoobdel et al [26] (2020) had reported that the odour of peanut butter, especially the roasted type, significantly attracted the German cockroaches [26]. Thus, the odour of roasted peanut could dramatically enhance bait attractiveness (Table 5) but did not enhance the bait consumption rate [27]. Ibrahim et al [27] (2017), also reported that roasted peanut was highly attractive to both male and female cockroaches [27], but suggested that a mixture of roasted peanut, fresh coriander leaves, zucchini fruit and coriander oil attracted even more cockroaches than peanut butter [27].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Interestingly, the results of our food consumption analysis showed that very little peanut butter, especially the roasted form, was eaten, although Khoobdel et al [26] (2020) had reported that the odour of peanut butter, especially the roasted type, significantly attracted the German cockroaches [26]. Thus, the odour of roasted peanut could dramatically enhance bait attractiveness (Table 5) but did not enhance the bait consumption rate [27]. Ibrahim et al [27] (2017), also reported that roasted peanut was highly attractive to both male and female cockroaches [27], but suggested that a mixture of roasted peanut, fresh coriander leaves, zucchini fruit and coriander oil attracted even more cockroaches than peanut butter [27].…”
Section: Discussionmentioning
confidence: 73%
“…Thus, the odour of roasted peanut could dramatically enhance bait attractiveness (Table 5) but did not enhance the bait consumption rate [27]. Ibrahim et al [27] (2017), also reported that roasted peanut was highly attractive to both male and female cockroaches [27], but suggested that a mixture of roasted peanut, fresh coriander leaves, zucchini fruit and coriander oil attracted even more cockroaches than peanut butter [27]. Thus, bait attractiveness could potentially be further enhanced by including these odours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human-mediated activities and socio-economic status within communities contribute to the abundance and persistence of arthropod vector burdens and associated direct and indirect implications [ 34 , 35 ]. For instance, provision of suitable refugia across macro and microhabitats [ 37 ], proximity to several alternative hosts [ 38 ], poor living conditions [ 39 ], feeding preferences and host availability [ 40 ] are key in attracting and influencing population increases of arthropod vectors. However, in some arthropod vectors (e.g., lice), improved personal hygiene [ 41 , 42 ], enhanced socio-economic livelihood [ 43 ] and acquisition of appropriate knowledge [ 44 ] remain crucial in suppressing their burden.…”
Section: Introductionmentioning
confidence: 99%